CHARACTERISTICS OF MANGROVE VEGETATION COMMUNITIES AND ASSESSMENT OF THEIR HEALTH BASED ON THE MANGROVE HEALTH INDEX (MHI) AND NORMALIZED DIFFERENCE VEGETATION INDEX (NDVI) IN THE PULAU DUA NATURAL RESERVE AREA, BANTEN - Fauzia, Althofina
Nature reserves are natural sanctuary areas that possess unique flora, fauna, and ecosystems that require protection. Pulau Dua Nature Reserve or Bird Island has the characteristic of mangrove ecosystem with diverse species that serve as habitat for various local and migratory bird species, also providing protection for the surrounding areas. The quality of the mangrove ecosystem determines its productivity and role in maintaining coastal ecosystem. This study aims to determine the quality of the mangrove ecosystem in Pulau Dua Nature Reserve using the Mangrove Health Index (MHI) and Normalized Difference Vegetation Index (NDVI) approaches. Stratified Sampling technique was used to determine 35 study plots and vegetation analysis as well as the Mangrove Health Index (MHI) approach. The Normalized Difference Vegetation Index (NDVI) method utilized Sentinel Level 2A imagery to determine the vegetation density in the study area. The results of the study indicate that Avicennia marina dominates (INP 211.02%) and contributes to the mangrove health index value. The quality of mangrove vegetation based on MHI is 88% in the Moderate health category, 9% in the Excellent health category, and 3% in the Poor health category. Meanwhile, mangrove vegetation density based on NDVI is 79% in the Good density category, 14% in the Normal category, 5% in the Very Good category, 1% in the Poor category, and 1% in the Very Poor category. The correlation between canopy cover percentage and NDVI is positive and strong (r = 0.51). The regression model of canopy cover percentage using NDVI variables is significant but has a low coefficient of determination (R2 = 0.15).